Pengaruh Lingkungan Kerja Non Fisik Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Bharaduta Jaya Sakti Jakarta Selatan - Pratama Supriadi; Chotamul Fajri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study was to determine the effect of work stress and workload on employee turnover intention at PT Bharaduta Jaya Sakti, both partially and simultaneously. The method used in this study is an associative quantitative method. The population at PT Bharaduta Jaya Sakti was 85 respondents. The sample used in this study used a saturated sample, which means it is the same as the population of 85 people. The analysis in this study used the SPSS program version 25. The data analysis method used a simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial t test and simultaneous f test. The results of this study indicate that: There is a partial significant effect of work stress on employee turnover intention at PT Bharaduta Jaya Sakti. This can be proven because the work stress variable (X1) has a calculated T value of 13,257 > t table 1.989 with a significance level of 0.000 <0.05, so Ho1 is rejected and Ha1 is accepted. There is a partial significant effect of workload on employee turnover intention at PT Bharaduta Jaya Sakti. This is proven because the workload variable (X2) has a calculated t-value of 13,299 > t-table 1.989 with a significance level of 0.000 < 0.05. Therefore, Ho2 is rejected and Ha2 is accepted. There is a significant simultaneous effect of work stress and workload on employee turnover intention at PT Bharaduta Jaya Sakti. This is proven because the calculated f-value of 157,331 > f-table of 3.108 with a significance level of 0.000 < 0.05. Therefore, Ho3 is rejected and Ha3 is accepted. The coefficient of determination test results are indicated by an R-square value of 0.791, indicating that the work stress (X1) and workload (X2) variables contribute 79,1% to the turnover intention variable (Y), while the remaining 20,9% is due to other variables not examined in this study.